Distributed School Leadership, Perceptions & Practices - Abdalla, Amani Ahmed (2014)
The purpose of this study is to explore the concept of distributed leadership among Teachers and schools’ Principals, the variation between perceptions and practices and how distributed leadership can impact teaching and learning. There are several factors that affect distributed leadership practices in schools. This study has focused on the Teachers’ and Principals’ understanding of “shared” leadership. The aim was to reveal features that support schools’ Principals and to assess whether or not distributed leadership is well-practised in their schools. A mixed methodological approach was chosen comprising a study of literature and statistical data, a questionnaire, semi-structured interviews and observations. The data was then analysed and triangulated in order to provide effective and useful data. The analysis of the results reveals that all the respondents understand the concept of distributed leadership as they agreed that distributed leadership enhances the teaching and learning process. However, there is a gap between perception and practices of distributed leadership in their schools. These variations could be directly associated with school Principals as owners of distributed leadership practices, in particular, factors that relate to teaching and learning or review of practices and policies. However, some of these practices may not relate to Principals because Stakeholders or the School Board can be involved in major decisions or having insufficient budget for teachers’ training. On that basis, the study highlights such variations between perceptions and practices, as it explains their limitations and outlines further research suggestions.